2010
DOI: 10.1002/stem.431
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-137 Regulates Neuronal Maturation by Targeting Ubiquitin Ligase Mind Bomb-1

Abstract: A final step of neurogenesis is the maturation of young neurons, which is regulated by complex mechanisms and dysregulation of this process is frequently found in neurodevelopmental disorders. MicroRNAs have been implicated in several steps of neuronal maturation including dendritic and axonal growth, spine development, and synaptogenesis. We demonstrate that one brain-enriched microRNA, miR-137, has a significant role in regulating neuronal maturation. Overexpression of miR-137 inhibits dendritic morphogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
334
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(357 citation statements)
references
References 52 publications
(101 reference statements)
11
334
1
4
Order By: Relevance
“…At present there is a rather limited literature. It is considered to be enriched in neurones, particularly, in the dentate gyrus and it is thought to have multiple functions during different stages of neurodevelopment (Shi et al, 2010;Smrt et al, 2010;Szulwach et al, 2010). Two recent molecular studies indicate MIR137 is involved in multiple epigenetic mechanisms regulating the balance of neuronal proliferation and differentiation (Sun et al, 2011;Smrt et al, 2010;Szulwach et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At present there is a rather limited literature. It is considered to be enriched in neurones, particularly, in the dentate gyrus and it is thought to have multiple functions during different stages of neurodevelopment (Shi et al, 2010;Smrt et al, 2010;Szulwach et al, 2010). Two recent molecular studies indicate MIR137 is involved in multiple epigenetic mechanisms regulating the balance of neuronal proliferation and differentiation (Sun et al, 2011;Smrt et al, 2010;Szulwach et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, postmortem studies have indicated differential expression levels of several miRNAs in prefrontal regions in SCZ and BD vs healthy controls (Perkins et al, 2007;Forero et al, 2010;Kim et al, 2010;Beveridge et al, 2011). In terms of MIR137 specifically, normal levels of expression are required for regulating the balance of neuronal proliferation and differentiation (Sun et al, 2011;Shi et al, 2010;Smrt et al, 2010;Szulwach et al, 2010). Although the expression pattern has yet to be fully established, it is enriched in neurons, particularly in the dentate gyrus, a region implicated in psychiatric disorders and known to undergo neurogenesis into adulthood (Sempere et al, 2004;Smrt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The downregulated expression of miR-137 in brain cancer stem cells is necessary for self-renewal in glioma stem cells (33,34). miR-137 regulates neuronal maturation by targeting ubiquitin ligase Mind Bomb-1 (35). miR-137 is also down-regulated in the blood serum of Alzheimer disease patients (36).…”
mentioning
confidence: 99%